Government Bonds and Stock Market : Volatility Spillover Effect - Faniband, Muhammadriyaj; Faniband, Taranum (Indian Journal of Research in Capital Markets, 2021)
A new data set of government bond prices, that is, the Clearing Corporation of India Limited’s Broad Total Return Index (BTRI) was introduced in this paper. The Total Returns Index (TRI) provides the change due to both the price movements and accrued interest. TRI reflects the change in the index due to market capitalized weighted price movement and accrued interest. This paper investigated volatility spillovers between government bonds and the stock market in India by following the GARCH (1, 1). By using a broad weekly data set during 2004 – 2019, with a total of 835 observations, this paper addressed a key research question : Does the effect of volatility spillover exist between government bonds and Nifty ? Does causality exist between government bonds and Nifty ? The results of Granger causality indicated that BTRI did not Granger cause Nifty. Further, the reverse was also not true, meaning that there existed no lead-lag relationship between BTRI and Nifty. The squared residuals’ coefficient of Nifty had a positive sign but was insignificant, showing that there was no effect of volatility spillover from the Nifty to the BTRI. Hence, the volatility in Nifty did not influence volatility in the BTRI but vice versa, this statement is also not true. This research is mainly useful to those investors who invest in both government bond market and stock market.